2006
DOI: 10.1111/j.1365-2036.2006.03088.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral V2 receptor antagonist (RWJ‐351647) in patients with cirrhosis and ascites: a randomized, double‐blind, placebo‐controlled, single ascending dose study

Abstract: SUMMARYBackground RWJ-351647 is a selective V 2 receptor antagonist that inhibits vasopressin-induced water reabsorption in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…Thus, tolvaptan clearly acts as an aquaretic. Further, in this single-dose study no increase in blood pressure was observed, which could have theoretically occurred due to increased binding of AVP displaced from the V 2 R to the V 1A R. In a larger clinical trial (ACTIV in CHF; n = 254) chronic administration of tolvaptan for 25 days (30,45, and 60 mg once daily) resulted in a sustained decrease in body weight and urine osmolality and a slight increase in serum sodium (particularly in patients with hyponatremia at baseline) as compared to placebo [11]. No changes in heart rate, blood pressure, renal function, or serum potassium were observed.…”
Section: Tolvaptan (Opc-41061)mentioning
confidence: 66%
See 2 more Smart Citations
“…Thus, tolvaptan clearly acts as an aquaretic. Further, in this single-dose study no increase in blood pressure was observed, which could have theoretically occurred due to increased binding of AVP displaced from the V 2 R to the V 1A R. In a larger clinical trial (ACTIV in CHF; n = 254) chronic administration of tolvaptan for 25 days (30,45, and 60 mg once daily) resulted in a sustained decrease in body weight and urine osmolality and a slight increase in serum sodium (particularly in patients with hyponatremia at baseline) as compared to placebo [11]. No changes in heart rate, blood pressure, renal function, or serum potassium were observed.…”
Section: Tolvaptan (Opc-41061)mentioning
confidence: 66%
“…RWJ-351647 induces the expected diuresis and free water excretion in rats and cynomolgus monkeys after a single dose; 10-day administration in monkeys demonstrated no tolerance development [29]. In 24 patients with cirrhosis and ascites on stable doses of furosemide and spironolactone, single oral doses of RWJ-351647 (1, 2, and 5 mg) dose-dependently increased urine flow and free water excretion, and decreased urine osmolality, which was significant compared to placebo for the 5 mg dose [30].…”
Section: Rwj-351647mentioning
confidence: 87%
See 1 more Smart Citation
“…Several V 2 -receptor antagonists have also been evaluated for the treatment of other edematous disorders, including heart failure (lixivaptan and tolvaptan) [17, 18] and cirrhosis (lixivaptan, OPC-31260, and RWJ-351647) [19,20,21]. The V 2 -receptor antagonists may also hold promise in the treatment of polycystic kidney disease; a phase 3 clinical trial is underway to determine the efficacy and safety of tolvaptan in patients with autosomal dominant polycystic kidney disease [22].…”
Section: Introductionmentioning
confidence: 99%
“…73,74 In addition, other studies such as Okita and associates have suggested a dose-dependent improvement in ascites, lower extremity edema and tolerance to diuretics with tolvaptan, but further research is needed to confirm these findings. 60,61,76,79,80 Conivaptan, approved for only 4 days of intravenous use in the hospital, for euvolemic and hypervolemic hyponatremia, 81 has limited data on its safety and efficacy. [82][83][84] In general, conivaptan was well tolerated with the most common adverse reaction being infusion-site reactions.…”
Section: Clinical Associationsmentioning
confidence: 99%